Evaluasi Mutu Salep Dengan Bahan Aktif Temugiring, Kencur Dan Kunyit - Titik Lestari; Bambang Yunianto; Agus Winarso (Jurnal Kebidanan dan Kesehatan Tradisional, 2017)
Abstract : Quality Evaluation, Ointments, Kaemferia Galanga, Curcuma Domestica, Curcuma Heynena. Indonesia is a country with very high biodiversity. In the high diversity of the stored potential nutritious plants that can be explored and exploited further. Community began to realize the use of chemicals to cope with life problems, especially health problems, in addition to expensive, can also result in less side effects both for humans. This study used a extract Curcuma domestica, Kaemferia galanga, and Curcuma heynena as active ingredients skin ointments. This study intends to determine the third quality evaluation ointment. This type of research was descriptive. Quality evaluation results showed nearly the same physical properties, except for the parameters of the spread, and viscosity. Test result of physical standart compliant was organoleptic, pH, power spread and viscosity.